2013
DOI: 10.1111/eci.12047
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of the association between inflammation and atrial fibrillation

Abstract: Elevated plasma CRP concentration per se does not increase atrial fibrillation risk. Values obtained for CCL2 suggest that inflammation is probably a consequence of AF. Our data also suggest that the effect of the duration of the episode should be further studied in the assessment of the actual role of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…[ 19 ] were the first to show the relationship between AF and inflammation in CABG patients. More recent studies showed an increase in CRP and IL-6 levels in occurrence and presence of AF [ 20 ]. Dernellis et al .…”
Section: Discussionmentioning
confidence: 99%
“…[ 19 ] were the first to show the relationship between AF and inflammation in CABG patients. More recent studies showed an increase in CRP and IL-6 levels in occurrence and presence of AF [ 20 ]. Dernellis et al .…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we speculated that gallium-67 SPECT/CT revealed diffuse inflammation in the left atrium, which was useful for understanding that temporary inflammation due to confined myocarditis in the left atrium caused paroxysmal atrial fibrillation. Recently, associations between cardiac inflammation and atrial fibrillation have been reported [11], and inflammatory cells such as macrophages are recruited across atrial endocardium in atrial fibrillation [12]. We think gallium-67 accumulation in the left atrium is due to acute myocarditis because the serum antibody titer of cytomegalovirus was elevated in a few weeks, but we cannot deny the possibility that it is due to an idiopathic infiltration of inflammatory cells, which is considered to be one of the causes of atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the role of circulating inflammatory factors in atrial fibrillation, Wu et al conducted a meta-analysis based on observational studies [ 114 ] and evidenced that the presence of increased inflammation molecules (CRP, IL-6, and TNF- α ) was significantly associated with a greater AF risk in the general population. High levels of CRP, CCL2, and CXCL8 among patients with AF were found by several investigators [ 115 , 116 ]. Notably, elevated levels of CXCL8 detected in patients with permanent AF but not in patients with paroxysmal AF suggested a link between low-grade inflammatory reaction and long-lasting AF [ 116 ].…”
Section: Inflammation Chemokines and Cardiac Arrhythmiasmentioning
confidence: 92%